(untitled) (Medico Legal Update, 2020)
India is a nation which requires societal awakening in ample of affairs. The progress of a nation isn’t solitary indomitable by fiscal eminence nevertheless by the in general wellbeing of its populace and consequently, being a “developing country” necessitate communal development. There is prevalent ignominy enclosed to abortion in the nation. The abortion law in India restrain the “reproductive autonomy” of women and the provisions of the Act are being violative of the provisions of Constitution of India. Women subsequent to passing of MTP Act are also performing unsafe abortions which have adverse effect on their wellbeing. For that reason the legal status of abortion law need to be altered according to the current scenario. The research paper intended at scrutinizing the Act and suggestion that the legislature ought to uphold while amending the present Act.